Development of Electronic Modules Based on STEM to Train Students' Creativity: Validity and Practicality Analysis - Melisa Melisa; Eko Susilowati; Dewi Dewantara (Berkala Ilmiah Pendidikan Fisika, 2021)
The STEM-based electronic module is a systematic presentation of learning materials to support students' independence with an approach in four fields of knowledge: science, technology, engineering, and mathematics. This study aims to describe the feasibility of this STEM-based electronic module to train students' creativity. The specific objectives of this study are to describe: (1) The validity of the STEM-based electronic physics module; and (2) The practicality of the STEM-based physics electronic module. The type of research was ADDIE, with the subject of the trial of 27 students at class X Science-1 in a public high school in Banjarmasin City, South Kalimantan, Indonesia. Data collection was obtained from observations, interviews, questionnaires, and tests. This research was analyzed qualitatively and quantitatively. The research results showed that: (1) the validity of the STEM-based electronic physics module was in a "very good" category, and (2) The practicality based on the implementation of the Lesson plan was categorized as "moderately practical". The existing STEM-based electronic physics modules (Science, Technology, Engineering, and Mathematics) to train students' creativity are still not suitable for learning. So, it can be concluded that the STEM-based physics electronic module is feasible to train students' creativity, and the direct result of this research was that educators could evaluate methods and media that support online learning more effectively for each meeting, and the results of this study can be used as input for teachers and teacher candidates. The next step of this research is to apply methods, learning models that support STEM and sufficient time to train students' creativity which is expected to be applied to face-to-face learning.